(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
In line with the Extension Policy of the Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul (IFRS), the group PET Conexões – Gestão Ambiental develops, since 2010, extension actions based on dialogic interaction, which aim to impact on student education and social transformation. Using environmental education as the main strategy, the group has been seeking to contribute to the construction of a more sustainable society, involving schools, vulnerable communities and the general public in its activities. The objective of this work is to register the actions carried out by the PET group in the year 2022, the first one after the pandemic period of COVID-19, in which the activities were again presential, although only partially. We report four actions related to the socio-environmental theme, which aimed at scientific dissemination and discussion. In the first of them, we sought to promote, within educational spaces, the discussion of the Climate Emergency theme. This was a face-to-face action that covered four educational institutions. The second action refers to the creation of a podcast for discussion of socio-environmental themes - the Balbúrdia Ambiental. In a similar way, an electronic magazine - PETNEWS - was created with the objective of divulging the Group’s actions internally and externally. Finally, the second edition of the Cycle of Socio environmental Debates was held, an event that approached the theme “food production in the context of urban space”. All actions were successful, reaching the expected amount of public and generating discussions that pointed to the prospect of continuing the projects, as well as to the promotion of other actions aimed at building environmental citizenship.